Russell speaking : original in Bangla Ami Russell bolchhi - Mijāna, Mijānura Rahamāna (Novel Publications, 1998)
Contributions of Sheikh Mujibur Rahman, 1922-1975, first president of Bangladesh, to the Bangladesh freedom movement; includes brief accounts of him and the assassination of his family.